Effects of Mindfulness-Based Cognitive Therapy on Stigma in Female Patients With Schizophrenia - Tang, Qiubi; Yang, Shuixian; Liu, Cuixia; Li, Liyan; Chen, Xiaodong; Wu, Fengchun; Huang, Xingbing (Frontiers in Psychiatry, 2021)
Mindfulness-based cognitive therapy (MBCT) has been increasingly recognized as effective in different mental illnesses, but these effects are limited in schizophrenia. For patients with schizophrenia, stigma is one of the most negative factors that affects treatment, rehabilitation and social function. This research aimed to determine the effects of MBCT on stigma in patients with schizophrenia. In total, 62 inpatients with schizophrenia were recruited and randomly assigned to the experimental group or control group. The experimental group received an eight-week MBCT intervention, and the control group were treated as usual. Link’s Stigma Scales (with three subscales, including perceived devaluation-discrimination (PDD), stigma-coping orientation, and stigma-related feeling), Five Facet Mindfulness Questionnaire (FFMQ), and Insight and Treatment Attitudes Questionnaire (ITAQ) were used to collect data before and after intervention. After intervention, the post-test score of PDD, stigma-coping orientation, FFMQ, and ITAQ were significantly different between the experimental group and the control group. In the experimental group, the PDD and stigma-coping orientation scores significantly decreased, and FFMQ and ITAQ scores increased remarkably (P<0.05). In addition, correlation analysis revealed a significant negative correlation between mindfulness and stigma. MBCT was effective in reducing stigma in patients with schizophrenia, which mainly manifested as changes in the patients’ perception of stigma as well as the withdrawal and avoidance caused by schizophrenia. Enhancing mindfulness will help reduce the stigma level. MBCT is worthy of promotion and application in patients with schizophrenia.